Promoting Awareness of Civil and Political Rights: Socialization in Lontar Tirtayasa Village, Serang Banten - Danial Danial; Hilton Tarnama Putra Manulang (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2022)
In terms of political involvement and contestation, civil and political rights can be a perfect measure of political democracy. Indonesia must report its steps to put the ICCPR's provisions into effect as part of its commitment to become a state party. One of the actualizations of the ICCPR's grassroots implementation relates to the socialization of civil and political rights of the community at the village level. The Abdimas team from the International Law Department, Law Faculty, Universitas Sultan Ageng Tirtayasa chose Lontar Village in Tirtayasa as the focus of their legal community service projects.